Evaluating Self-Pollination Methods: Their Impact on Nut Set and Nutlet Abscission in Macadamia - Palakdeep Kaur; Max Cowan; Joanne De Faveri; Mobashwer Alam; Bruce Topp (Plants)
Nut set is an important determinant of yield and plays a pivotal role in orchard profitability. The complex process of nut setting is governed by numerous factors, with pollination being a critical mechanism. Macadamia cultivars exhibit both self- and cross-pollination. Self-pollination may increase nut set, so it is a trait of interest in breeding. This study investigated nut setting and nutlet abscission on four cultivars, ‘HAES 791’, ‘HAES 741’, ‘HAES 344’, and ‘A16’, using three controlled self-pollination methods: (i) autogamy (AG), entailing bagging before anthesis with no hand-pollination; (ii) geitonogamy 1 (GG1), bagging following hand-pollination using pollen from the same raceme; and (iii) geitonogamy 2 (GG2), bagging following hand-pollination using pollen from different racemes of the same cultivar. These self-pollination methods were compared against open-pollination (OP). ‘HAES 741’ and ‘HAES 791’ were partially self-fertile, while ‘HAES 344’ and ‘A16’ were self-infertile. Final nut sets per raceme for ‘HAES 741’ were 0.43 by AG, 0.65 by GG1, and 0.5 by GG2, and for ‘HAES 791’, they were 0.90 by AG, 1.25 by GG1, and 1.0 by GG2. Final nut set per raceme with OP was higher compared to self-pollination methods and ranged between 3.5–6.5. In self-fertile cultivars, nut set following the three self-pollination methods accounted for 6.5–3.7% of the nut set following OP, and nutlet abscission following self-pollination methods accounted for 20–50% of nutlet abscission following OP. No significant differences in nut set and nutlet abscission were observed among AG, GG1, and GG2. Results suggest that macadamia orchards planted with self-fertile cultivars would be less reliant on external pollinators or artificial pollination to achieve adequate yields.